Increased matrix stiffness promotes fibrogenesis of hepatic stellate cells through AP-1-induced chromatin priming - Wenxue Zhao; Weihong Yuan; Tian Dong; Wei Qi; Zhijie Feng; Cheng Li; Yujie Sun (Communications Biology)
Abstract Matrix stiffness has significant effects on cell behavior, however, less is known regarding the epigenomic and transcriptional regulation underling the effect of matrix stiffness on cells. In this study, we use an in vitro system to assess the phenotypic shifts of hepatic stellate cells (HSCs) following changes in matrix stiffness, and integrate multi-omics with imaging and biochemical assays to investigate the molecular mechanisms. We show that cells cultured on a stiff matrix display more accessible chromatin sites, which consist of primed chromatin regions that become more accessible prior to the upregulation of nearby genes. These regions are enriched in fibrosis-associated genes that function in cytoskeletal organization and response to mechanical stimulus. We also identify activation of p-JUN in response to the stiff matrix and promoting phenotypic shifts. The identified chromatin accessibility-dependent effect of matrix stiffness may be responsible for various fibrotic diseases and provide insight into intervening approaches.